Counter-hegemonic proposals in teacher training - Rivas-Flores, José Ignacio (My University, 2018)
Teacher education in Spanish Universities is suffering the slow but steady progress of neoliberal proposals in education. Academic excesses, highly scholarized model, strong protocolization of their proposals, exacerbated control of educational practices, ... This change comes hand in hand with an important regression in the educational theoretical and ideological frameworks, both in the academic and scientific world, as in educational policies and school practices. Given this situation we present some counterhegemonic practices with which we are trying to break this inertia and starting another teacher education model. For that we start from some premises: on the one hand, the engagement of teacher education colleges with schools in educational system; it is necessary to understand all levels of education as a unit, as a transformative, political and emancipatory practice. On the other hand, we raise the need for future teachers to be part of alternative educational proposals, allowing their education as teachers take place from experiences of social and educational change. By last, a change in educational thinking that breaks with the theory-practice dichotomy is necessary, based on another theory of knowledge from the critical socio-constructivist perspective, in which both dimensions are re-constructed as a single entity.
Keywords: Enseñanza - Congresos; Neoliberalismo; Formación del profesorado; Educación crítica